"When that understanding is there, you work much better together": the role of family in audiological rehabilitation for older adults. (2nd December 2022) - Scarinci, Nerina; Meyer, Carly; Hickson, Louise
Abstract: Objective: This study aimed to explore the experiences and perceptions of adults with hearing impairment and family members regarding the role of family in audiological rehabilitation. Design: A qualitative descriptive methodology was used. Study Sample: A total of 37 people participated, 24 older adults with hearing impairment and 13 family members (11 spouses and 2 adult children). Four focus group interviews were conducted with the adults with hearing impairment, and 3 with family members. Results: Five key themes emerged from analysis of the transcripts: (1) knowledge and understanding of hearing impairment and treatment; (2) the role of family members in rehabilitation is complex and multifaceted; (3) audiologists have an influential role in facilitating family member involvement; (4) the role of communication in rehabilitation; and (5) outcomes of family member involvement. Importantly, although perceptions were generally very positive, there was some uncertainty about the role of family. Conclusions: Audiologists have a key role in facilitating family involvement in audiological rehabilitation that is identified by adults with hearing impairment and their families. Although participants reported limited involvement in audiological rehabilitation currently, they identified potential for involvement in areas such as goal setting and decision-making.